GLOBALIZATION AND STATE SOVEREIGNTY - Jadwiga Kossowska (Defence Science Review, 2017)
Increasing globalization and integration in Europe, posed in a new light the problems associated with sovereignty and identity of nations. Becoming a participant in international relations voluntarily limit its sovereignty. Today, the traditional understanding of sovereignty is not responsible ways of achieving the objectives, interests and functions of the state. The article analyzes the process of globalization in terms of its impact on the sovereignty of the state.